Synthesis and virtual screening of bis-(4-(tert-butyl)-N-(methylcarbamothioyl) benzamide)-Iron (III) complex as an anticancer candidate - Ruswanto Ruswanto; Winda Trisna Wulandari; Richa Mardianingrum; Indah Cantika (Pharmaciana, 2021)
Thiourea derivatives were much used in drug discovery and drug-making, such as for an anticancer. The formation of drug complexes can increase lipophilicity through chelation formation, and the drug action is significantly upward due to the effective permeability to the center. In another study, the alteration of the compound becomes the complex with metal will grow in its activity so recently we have synthesized the Bis-(4-(Tert-Butyl)-N-(Methylcarbamothioyl) Benzamide)-Iron (III) complex.Â  The synthesis of Fe (III) metal with the 4-(Tert-Butyl)-N-(Methylcarbamothioyl) Benzamide in ethanol by reflux at 75oC for 7 hours. Hot Stage Microscopy, UV-Visible Spectrophotometry Infrared Spectrophotometry, and Massa Spectrophotometry were used to characterize the complex. This study concerns representing, inferring, and predicting pharmacokinetics and toxicity and molecular docking complexes. The complex weight was 0.29469 g. Its purity has been tested using the melting point determination and has obtained its range was 113o-115oC. The Characteristics of Bis-(4-(Tert-Butyl)-N-(Methylcarbamothioyl) Benzamide)-Iron(III) complex have a maximum wavelength of 260,0 nm and provide absorption of Fe-O vibrations at wavenumbers 478,2 cm-1and 588 cm-1, and the m/z complex of spectrophotometry mass was 559,31. The molecular docking process was performed using AutodockTools-1.5.6 software. It showed that Bis-(4-(Tert-Butyl)-N-(Methylcarbamo-thioyl)Benzamide)-Iron(III) complex could interact with ribonucleotide reductase enzyme, and it has better interaction than the 4-(Tert-Butyl)-N-(Methylcarbamothioyl)Benzamide with the binding affinity energy (Î”G)of Â -8,52 kcal/mole and the constant inhibition (Ki ) of 568,55 nM.